ESP Lesson Design Through Lesson Study: Insights from a School-University Partnership in Indonesia - Hakim, Lystiana Nurhayat; Muliyah, Pipit (Universitas Hamzanwadi, 2025)
Designing effective English for Specific Purposes (ESP) lessons in vocational schools remains a challenge, as teachers often struggle to source authentic materials, align content with workplace demands, and collaborate across disciplines. This study investigates the collaboration between vocational English teachers, university students, and lecturers in developing ESP lesson designs. It utilized the school–university partnership-based Lesson Study framework (Plan, Do, See) across twelve meetings in Indonesian vocational schools. A qualitative–quantitative design was employed with five English teachers, three lecturers from English education, agriculture, and farming, and thirty-five pre-service teachers. Data were collected through observations, a self-developed questionnaire that was content-validated by professors in a private university, semi-structured interviews, and field notes, and analyzed thematically and descriptively. Survey results show that over 85% of participants agreed or strongly agreed that lesson study enhanced their ESP lesson planning, improved their understanding of students’ needs, and strengthened collaboration with colleagues. Interviews and observations corroborated these findings, highlighting that lesson study fostered trust, professional community, and greater confidence in integrating authentic workplace materials. Pre-service teachers reported improved ability to connect theory with practice, while lecturers enriched lesson design with subject-specific expertise. Challenges included selecting suitable syllabus topics, sourcing authentic ESP materials, and managing online delivery. The study demonstrates that school–university partnerships through lesson study provide an effective model for enhancing ESP pedagogy and professional development, supporting teacher autonomy and preparing pre-service teachers with collaborative competencies for future careers.